Salted paper printing : a step-by-step manual highlighting contemporary artists - Anderson, Christina Z. (Contemporary practices in alternative process photography series., 2018)
"Salted Paper Printing: A Step-by-Step Manual Highlighting Contemporary Artists makes one of the oldest known photographic processes easy for the 21st century using simple digital negative methods. Christina Z. Anderson's in-depth discussion begins with a history of salted paper printing, then covers the salted paper process from beginner to intermediate level, with step-by-step instructions and an illustrated troubleshooting guide. Including cameraless imagery, hand-coloring, salt in combination with gum, and printing on fabric, Salted Paper Printing contextualizes the practice within the varied alternative processes. Anderson offers richly-illustrated profiles of contemporary artists making salted paper prints, discussing their creative process and methods. Salted Paper Printing is perfect for the seasoned photographer looking to dip their toe into alternative processes, or for the photography student eager to engage with photography's rich history."--